Novel metabolite madeirone and neomarinone extracted from Streptomyces aculeoletus as marine antibiofilm and antifouling agents - Wissner, Julian L.; Almeida, Joana R.; Grilo, Inês R.; Oliveira, Jhenifer F.; Brízida, Carolina; Escobedo-Hinojosa, Wendy; Pissaridou, Panayiota; Vasquez, Marlen I.; Cunha, Isabel; Sobral, Rita G.; Vasconcelos, Vítor; Gaudêncio, Susana P. (Frontiers in Chemistry, 2024)
Biofouling presents a significant economic threat to various marine industries, resulting in substantial financial losses that can amount to billions of euros annually. This study addresses the pressing need for effective alternatives to traditional antifouling agents, especially in the aftermath of the global prohibition of organotin compounds.Our research highlights the importance of madeirone (1), a novel marinone derivative discovered in the framework of this study, and neomarinone (2), both isolated from Streptomyces aculeolatus PTM-346, as potent inhibitors of both micro and macrofouling marine species. Madeirone (1) displayed significant antibiofilm efficacy inhibition against Phaeobacter inhibens (up to 66%),